Psychological Factors Associated with Relapse in Psychotic Patients attending Teaching Hospitals in AL_Furat Al-Awsat Governorates) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Relapse demonstrates a large problem in general health; the relapse effects on the family andthe client together social contact with other people and financially.Objectives: To find out the relationship between the Psychological factors of relapse and sociodemographicdata of psychotic patients attending teaching hospitals in AL_Furat Al-Awsat Governorates.Methodology: The design was (Descriptive-Correlational) used to describe the variables and therelationships that occur among them in this study. The sample was (a non-probability) purposive of (181)relapsed psychotic patients were selected from our patients centers from teaching hospitals in AL_FuratAl-Awsat Governorates, during the period from 9th May 2019 to 20th August 2019. The instrument includedtwo parts: sociodemographic variables and the psychological factors associated with relapse. The researcherused descriptive statistics tools such as frequency, percentage, mean of score and used in inferential statisticssuch as Chi-Square.Results: The findings of the study indicate that (45.86%) of the sample their diagnosis was schizophrenia,(25.97%) were schizoaffective and (11.60%) were major depressive disorder with psychotic features. Also,the findings of the study indicate that (39.2%) of the study samples they have poor psychological factors,(34.8%) they have moderate psychological factors and (26%) they have good psychological factors.Conclusion: There is a high significant relationship between the most sociodemographic data andpsychological factor (that included high express emotion and stigma factors).